Частотний вiдгук подвiйних кiльцевих резонаторiв при рiзних типах збудження в Ка-дiапазонi - Chornyi, V. S.; Skripka, S. L.; Nechyporuk, O. Y. (Publishing house "Academperiodika", 2019)
The frequency response of split-ring resonators (SRRs) at different types of excitations in the Ka-band has been investigated. The constructive parameters of SRRs are obtained from the electromagnetic simulation. Two unilateral and two bilateral samples of SRRs are experimentally investigated at the magnetic or electric excitation and a combination of both types of excitation. In order to get the widest resonance band, it is necessary to use a combination of magnetic and electric excitations. The resulting resonance width is 10 GHz. It is demonstrated that bilateral structures, despite the theoretical assumptions, may get a residual electric resonance. Since the depth of the resonance is less than -6 dB, it can be neglected, but the influence of combining two excitations must be taken into account.